Evaluation of short-term effectiveness of the disease management program “Di.Pro.Di.” on continuity of care of patients with congestive heart failure - Pecchia, Leandro; Schiraldi, Fernando; Verde, Sossio; Mirante, Enrico; Bath, Peter A.; Bracale, Marcello (2010)
This paper aimed to assess the early effectiveness of a disease management program (DMP), called “Dimissione Protetta Difficile” (Di.Pro.Di) conducted by personnel from the intensive care unit (ICU) of Public Hospital S. Paolo, Naples, Italy. Di.Pro.Di significantly reduces the number and risk of rehospitalizations and total hospital length of stay.